Vagus Nerve: Learn How to Reduce Inflammation, Prevent Chronic Illness and Overcome Anxiety, Stress and Depression, Activating and Stimulating The Most Important Nerve in Your Body - Supran, Stephen (Independently published, 2020)
Do you suffer from any digestive problems, heart related problems, depression, anxiety, chronic inflammation, stress, anxiety and other related problems? If so, would you like to finally put an end to your suffering and improve your overall physical and mental health? If so, then keep reading… You Are About To Discover How To Unlock The Secret Healing Powers Of The Longest And Most Complex Nerve In Your Body, The Vagus Nerve, To Heal From Chronic Inflammation, Stress, Anxiety, Depression And Much More! Wandering from the base of the brain then branching through your lungs, heart, digestive tract and all the way to your abdomen, the vagus nerve is the longest and most powerful of the cranial nerves in your body, making it the most important nerve you never knew you had. It works as some sort of ‘superhighway’ that carries all manner of information to and from the organs and organ systems connected in its complex network. And it is the reason why your stomach curdles when you feel threatened, why your heart races, your lungs slow down and the reason why your body generally slows down. So if anything disrupts the flow of information in this ‘superhighway’, you can bet that there will be all manner of problems. These problems manifest in the form of anxiety, chronic inflammation, stress, unusual heart rate, pain in the ear, digestive problems, difficulty speaking or loss of voice, abdominal pain, bloating, abnormal blood pressure, nausea, vomiting and much more! So if you’ve been experiencing these problems (symptoms) and have tried all manner of solutions to deal with the symptoms without any lasting effects, you need to consider the possibility that the problem lies with your vagus nerve and work on fixing the problem from its root. And this book will teach you just that! Perhaps you're wondering… What makes the Vagus Nerve so special? Which are the main organs that it comes into contact with? What are the health problems associated with a dysfunctional Vagus Nerve? And what can you do to improve the functioning of the vagus nerve to deal with all the associated problems? If you have any of these questions and any other related questions, this book is for you so keep reading. More precisely, you will learn: The medicine used to stimulate the Vagus Nerve How to effectively deal with depression, anxiety, addiction, depression, irritability and insomnia through your vagus nerve What inflammation is, how it occurs in your body and how to fight it with all manner of solutions, including through your diet How to control inflammation and pain in your body All about the glossopharyngeal nerve and the vagus nerve and the disorders associated with them What a chronic illness is and how you can prevent chronic illness by healthy eating How chronic illness is a disability as well as how to live with a chronic disease The causes of chronic illness, including the place of our lifestyle in causing chronic illnesses Mindful ways to make life better again and tips to bypass chronic illness Natural ways of overcoming anxiety without using medication Mindfulness psychotherapy for overcoming anxiety And much more Yes, even if you feel the problems you are struggling with are not related to your vagus nerve, you will be surprised to realize that there is a connection so don’t let the opportunity to do something about your health pass you!